Viscoelasticity of biological materials - measurement and practical impact on biomedicine - Kucharová, M; Doubal, S; Klemera, P; Rejchrt, P; Navrátil, M (Physiological research, 2007)
Mechanical behavior of biological structures under dynamic loading generally depends on elastic as well as viscous properties of biological materials. The significance of "viscous" parameters in real situations remains to be elucidated. Behavior of rheological models consisting of a combination of inertial body and two Voigt's bodies were described mathematically with respect to inverse problem solution, and behavior in impulse and harmonic loadings was analyzed. Samples of walls of porcine and human aorta thoracica in transverse direction and samples of human bone (caput femoris, substantia compacta) were measured. Deformation responses of human skin in vivo were also measured. Values of elastic moduli of porcine aorta walls were in the interval from 10(2)kPa to 10(3) kPa, values of viscous coefficients were in the interval from 10(2) Pa.s to 10(3) Pa.s. The value of shear stress moduli of human caput femoris, substantia compacta range from 52.7 to 161.1 MPa, and viscous coefficients were in the interval from 27.3 to 98.9 kPa.s. The role of viscous coefficients is significant for relatively high loading frequencies - in our materials above 8 Hz in aorta walls and 5 Hz for bones. In bones, the viscosity reduced maximum deformation corresponding to short rectangular stress.
Keywords: senioři; točivý moment; viskozita; Elasticity; Bone and Bones; Middle Aged; mužské pohlaví; aorta thoracica; Viscosity; tlak; Pressure; Adult; Sus scrofa; Stress, Mechanical; Rheology; Models, Biological; pružnost; Skin Physiological Phenomena; kosti a kostní tkáň; Torque; ženské pohlaví; zvířata; Humans; fyziologie kůže; lidé středního věku; biologické modely; mechanický stres; reologie; dospělí; Female; Aged; Aorta, Thoracic; lidé; Male; Animals